The Phenolic Content and Antioxidant Capacity of Pumpkin, Rosehip and Pomegranate Seeds - Sena Bakır (Turkish Journal of Agriculture: Food Science and Technology)
Food waste is a significant problem worldwide. These food wastes, often discarded without any preliminary processing, can be rich in bioactive substances. In this study, the aim was to identify the phenolic compounds in pumpkin, rosehip and pomegranate seeds, which are frequently consumed in winter. For this purpose, ultrasonically assisted methanolic extracts were prepared from seeds separated from other waste parts (such as shells, stems, and leaves). The results indicated that pomegranate seeds had the highest total phenolic content, with 45.6±3.1 mg GAE/g sample (P<0.05). Similarly, pomegranate seeds also showed the highest total antioxidant capacity in both CUPRAC (114.7±2.6 mg torolox/g sample) and DPPH (71.2±3.8 mg torolox/g sample) analyses (P<0.05). In phenolic profiling analysis using HPLC-PDA, syringic acid was the most abundant compound in pumpkin seeds, (-)-catechin in rosehip seeds, and punicalagin derivatives in pomegranate seeds.